Alternative Dispute Resolution for Violations of The Conditional Divorce (Taklik Talak) as Grounds for Divorce in Islamic Family Law in Indonesia - Putri Rahma; Mhd. Yadi Harahap; Abd. Mukhsin (MISYKAT AL-ANWAR JURNAL KAJIAN ISLAM DAN MASYARAKAT, 2026)
This study aims to analyze the status of taklik talak in Islamic family law in Indonesia, the breach of taklik talak as grounds for a divorce suit, and alternative dispute resolution methods that can be pursued. The method used is normative legal research with a legislative and conceptual approach. Data were obtained through a literature review covering primary, secondary, and tertiary legal sources, and were then analyzed using a descriptive-analytical qualitative approach. The results of the study indicate that taklik talak holds an important position as a legal protection mechanism for wives and can serve as the basis for a divorce suit in the event of a breach of the agreement’s terms. Common forms of breach include abandonment, failure to provide financial support, domestic violence, and unfair treatment within the household. Dispute resolution can be pursued through non-litigation channels such as negotiation, family mediation, and the BP4 (Family Mediation Board), as well as through litigation in the Religious Court if an amicable settlement cannot be reached. The case study of the Lubuk Pakam Religious Court Decision No. 174/Pdt.G/2012/PA.Lpk confirms that a violation of the conditions of divorce (taklik talak) has valid legal consequences as grounds for divorce.